An Investigation of the Relationship Between Psychological Resilience Levels and Goal Commitment of Athlete Students - Yavuz Selim AĞAOĞLU; Mehmet KARGÜN (ümit doğan üstün, 2023)
This study was designed to examine the relationship between psychological resilience and goal commitment of student-athletes. The research was designed by adopting the relational survey model, one of the nice research methods. Brief Psychological Resilience Scale and Goal Commitment Scale were used as data collection tools. The research group consisted of 223 students, 121 of whom were male and 103 of whom were female. IBM SPP 25.0 package program was used for statistical processing of the data obtained from the student-athletes. After the statistical procedures, a significant difference was found in the psychological resilience and goal commitment levels of student-athletes according to the variables of gender and the type of sport of interest. The high level of positive relationship between psychological resilience and goal commitment scales and the fact that psychological resilience is an important and significant predictor of goal commitment are important results of the study.